Determinants of Under-Five Child Mortality in Ethiopia: Analysis Using Ethiopian Demographic Health Survey, 2016 - Addisalem Tebeje Zewudie; Abebaw Addis Gelagay; Engidaw Fentahun Enyew (International Journal of Pediatrics)
Background. Under-five mortality rate is a leading indicator of the level of child health and the overall development in countries which indicate the quality of life of a given population, as measured by life expectancy. Objectives. To identify and analyze factors that may have a significant influence on under-five mortality in Ethiopia. Methods. A national representative cross-sectional study and a quantitative study were conducted among 18,008 households selected based on 2016 EDHS data. The analysis was done using SPSS version 20 statistical software. Both bivariate and multivariable analyses were employed. In multivariable analysis, p value less than 0.05 was considered statistically significant and odds ratio with 95% CI (confidence interval) was used to assess the determinants of under-five child mortality. Results. A total of 10,641 children were included in the study with a 99.0% response rate. The U5CM for being a rural resident (AOR=1.802, 95% CI: 1.251, 2.595), not breastfeeding (AOR=2.956, 95% CI: 2.490, 3.511), having multiple birth (AOR=4.755, 95% CI: 3.440, 6.572), male gender (AOR=1.363, 95% CI: 1.153, 1.612), having first birth order (AOR=1.592, 95% CI: 1.275, 1.992), and having family size six and above (AOR=2.187, 95% CI: 1.769, 2.707). The increment of family size increases the risk of U5CM.Conclusion. Multivariate logistic analysis reflected that place of residence, mothers’ educational level, religion, current breastfeeding status, type of birth, sex of child, birth order, and family size were found to be significant predictors of under-five child mortality. So, government policy, nongovernmental organizations, and all concerned bodies should be focused on the major determinants of under-five child mortality and put in a lot more effort to reduce under-five child mortality, and health intervention policies should be revised.